The effect of surgery in neonatal hepatitis - E. M. Halimun (Indonesian Pediatric Society, 1984)
A review of nine neonatal hepatitis cases, which underwent exploratory laporatomy in the course of the disease, gave the conciusion that surgical intervention did not give unfavourable effect to the patients. Irrigation of the bile trees provoked bile flow and produced a normal serum bilirubine 3 months after surgery. However, this procedure did not suggest that insidious progression of cirrhosis could be arrested.